Transforming apricot kernel shell into a multifunctional photocatalyst for wastewater treatment and antimicrobial applications - Lian, Faqin; Batool, Fareena; Anjum, Muzammil; Qadeer, Samia; Idris, Abubakr M.; Nisa, Waqar-un-; Rao, Zepeng; Ullah, Habib (Frontiers in Environmental Science, 2025)
Introduction: Industrial wastewater (WW) has emerged as one of the significant environmental problems posing serious concerns to aquatic and human health. Among various industries, pharmaceutical compounds have been detected in various aquatic environments and food supply chains; therefore, they need an economical and efficient treatment process. Photocatalysis is a promising technology for addressing environmental pollution, such as wastewater treatment and microbial disinfection. Methods: In this study, a novel visible light-active photocatalyst was developed using activated carbon (AC) derived from local biomass; apricot kernel shell (AKS) and modified with Ag2O/ZnO, The synthesized phototcatalyst (AC/Ag2O/ZnO) was characterized by using various tools such as XRD, UV-Visible spectroscopy and FTIR. Extensive experiments were performed to test AC/Ag2O/ZnO for its multi-application potential, such as degradation of selected organic pollutants, treatment of pharmaceutical WW and heavy metal removal, and microbial disinfection. In the first set of experiments, the reactive black azo dye was used as the selected model pollutant and optimized for various operating conditions such as time, pH, pollutant concentration, and catalyst dose. In the second phase, pharmaceutical WW was treated using a photocatalysis process compared to photolysis (without catalyst). The third experimental setup, AC/Ag2O/ZnO was evaluated for its disinfection potential against common pathogens, including Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Results and Discussion: The results demonstrated up to 99% removal of reactive black azo dye within 4 h under optimum operation conditions, i.e., pH of 5.0, pollutant concentration of 10 ppm, and a catalyst dosage of 0.5 g/L. In the case of pharmaceutical WW, a significant reduction in chemical oxygen demand (COD) from 1195 to 199 mg/L was achieved, outperforming photolytic treatment, which reduced 1283.5 mg/L to 956 mg/L. The antimicrobial activity test showed efficient bacterial inhibition, with the zone of inhibition (ZOI) measuring 7 mm for E. coli, 12 mm for S. aureus, and 7 mm for P. aeruginosa. Overall, this research highlights the potential of activated carbon-based photocatalysts in addressing critical environmental challenges through efficient pollutant removal and antimicrobial action, contributing to sustainable WW treatment solutions. The findings will be very advantageous in developing an efficient wastewater treatment process, evaluating its upscaling potential, and serving as a framework for field application.